Development of HDTMA-modified Philippine natural zeolite (PNZ) for sulfamethoxazole adsorption - Ethan Angelo P Gaw; Julius Andrew P Nuñez (Materials Research Express)
The surface of Philippine natural zeolites (PNZs) was modified using the surfactant hexadecyltrimethylammonium chloride (HDTMA-Cl) to improve its adsorption capacity of sulfamethoxazole (SMX), a persistent organic pollutant and emerging contaminant. The PNZs were modified with HDTMA based on their 100% and 200% external cation exchange capacity (ECEC) to form monolayer and bilayer HDTMA–modified zeolites (MHZ & BHZ). The unmodified zeolites (UZs) and surfactant–modified natural zeolites (SMNZs) were characterized using Fourier Transform Infrared Spectroscopy, Thermogravimetric Analysis-Derivative Thermogravimetry, Scanning Electron Microscopy with Energy Dispersive x-ray Spectroscopy, and X-Ray Diffraction to confirm the modification of the PNZs using HDTMA. The SMX adsorption of UZ and SMNZs were fitted using isotherm and kinetic models. It was determined that all zeolites showed a high degree of linearity relative to the Langmuir, Freundlich, and Temkin models. The maximum SMX adsorption of MHZ and BHZ was calculated to be 3.685 mg g ^−1 and 13.034 mg g ^−1 , respectively, exhibiting 1.6 times and 5.5 times more improved SMX adsorption than UZ. Kinetic models showed that UZ and SMNZ adhered to the pseudo-second order model. The results of this study highlight the promising increased SMX adsorption using SMNZs.